(3TQM Ydi GdRGjQLI GdSHJjIs - (3CHhGdYHGS CMeO GdSHJjs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejfJ hHYO agPg GdWQjbI JOd Ydi eG Naj ef GdCSFdI s
(3BNQgG (B:s
(3aGcJeg Yf ef GJi GfJgi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B50s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B(58 (3c(B) s
Keywords: (3GdMQha h GdChaGbs